ANALYSIS OF PHYSICAL PROPERTIES OF GYPSUM PANELS FROM BANANA BOARD WASTE MATERIAL - Ety Jumiati; Abdul Halim Daulay; Nurhayati Nurhayati (Universitas Islam Negeri Sumatera Utara Medan, 2021)
Abstract. Research has been carried out which aims to determine the manufacture and physical properties of gypsum panels in the manufacture of gypsum panels for home interiors using banana midrib waste which is converted into fiber. Variations in the composition of mixing gypsum flour with banana midrib fiber include: Samples (A: 0%:100%) , (B: 2%:98%), (C: 4%:96%), (D: 6%:94 %), (E: 8%: 92%), and (F: 10%: 90%) with a FAS of 0.5. The physical test parameters include: Density, Water absorption, and Thickness expansion. From the test results obtained gypsum panels that are The best is in sample B which has a density value = 1.19 g/cm3, water absorption value = 24%, a thickness expansion value = 2.53%, which has complied with SNI 01-4449-2006 on the ceiling board. Key words: Gypsum panels, banana midrib, and gypsum flour.